Japanese law - Oda, Hiroshi, 1952- (Oxford : Oxford University Press, 2021)
This text covers the entire range of Japanese law with an emphasis on commercial law covering such topics as the reform of the company law, internationalisation of competition law, the financial big bang, and cross-border litigation.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 10, 2021).
Keywords: Law -- Japan